(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
This article presentes na analysis of the urban intervention How far the eyes reach, conceived by Grupo Balde and whitin the scope of NETOC/GPHPC/UFSJ based on the book Mujeres/Womens by Eduardo Galeano. The work carried out in the São João del-Rei city and had the investigacion of light as the protagonista of the creative process and composition as na objective of the place, understanding that the perception of light and color, establishing irself in the scene as landscape-ligth.For this dialogic perspective, we also seekk to question the limits between the creative process and the spetacularized scenic and the ways in which both are stablished in urban intervetions.